2009
DOI: 10.1111/j.1399-302x.2009.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in the oral cavity is associated with gastroesophageal disease

Abstract: H. pylori detection in the oral cavity is associated to gastroesophageal disease. In addition, it is suggested that all patients presenting gastric symptoms and H. pylori detection in the oral cavity would begin bacterial treatment immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
(53 reference statements)
3
18
1
2
Order By: Relevance
“…A large number of PCR systems used for the detection of H. pylori DNA in gastric biopsy samples and oral samples have been reported (Silva et al, 2009;Morales-Espinosa et al, 2009). With the exception of H. pylori, very few bacteria are observed in gastric lesions because of the highly acidic pH (Hirai et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of PCR systems used for the detection of H. pylori DNA in gastric biopsy samples and oral samples have been reported (Silva et al, 2009;Morales-Espinosa et al, 2009). With the exception of H. pylori, very few bacteria are observed in gastric lesions because of the highly acidic pH (Hirai et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggests and could expands on that theory by demonstrating that not only are oral-sexual behaviours important, but m mmon habits, such as smoking or drinking alcohol, may also contribute to the HPV infection to the oral region. It could be interesting to evaluate whether the oral cavity could be not only the reservoir for HPV, but for other pathogens [47]. The results of the present investigation showed a high frequency of HPV (67%) infection in the oral and genital mucosas, suggesting that patient's habits could contribute to the infection; and they suggest that the mode of viral transmission.…”
Section: Pv-dn Hmentioning
confidence: 69%
“…Moreover, on the basis of PCR results, some authors have suggested that saliva and dental plaque may serve as a temporary reservoir for H. pylori in individuals with gastric disease (Silva et al, 2009). Even an antibacterial treatment therapy was recommended by some researchers on the basis of positive PCR results of H. pylori in the oral cavity of patients with gastric symptoms, since the authors have suggested an association between the prevalence of H. pylori in the oral cavity and gastroesophageal disease (Morales-Espinosa et al, 2009). …”
Section: ; De Souza Gonçalves Et Al 2009)mentioning
confidence: 99%